GPCR heteromers: An overview of their classification, function and physiological relevance - Dale, Natasha C.; Johnstone, Elizabeth K. M.; Pfleger, Kevin D. G. (Frontiers in Endocrinology, 2022)
G protein-coupled receptors (GPCRs) are capable of interacting to form higher order structures such as homomers and heteromers. Heteromerisation in particular has implications for receptor function, with research showing receptors can attain unique expression, ligand binding, signalling and intracellular trafficking upon heteromerisation. As such, GPCR heteromers represent novel drug targets with extensive therapeutic potential. Changes to ligand affinity, efficacy and G protein coupling have all been described, with alterations to these pharmacological aspects now well accepted as common traits for heteromeric complexes. Changes in internalisation and trafficking kinetics, as well as β-arrestin interactions are also becoming more apparent, however, few studies to date have explicitly looked at the implications these factors have upon the signalling profile of a heteromer. Development of ligands to target GPCR heteromers both experimentally and therapeutically has been mostly concentrated on bivalent ligands due to difficulties in identifying and developing heteromer-specific ligands. Improving our understanding of the pharmacology and physiology of GPCR heteromers will enable further development of heteromer-specific ligands with potential to provide therapeutics with increased efficacy and decreased side effects.